Photostability and insecticidal activity of two formulations of granulovirus against Tecia solanivora larvae - CHAPARRO, MARTHA; ESPINEL-C., CARLOS; COTES P., ALBA MARINA; VILLAMIZAR-R., LAURA (Revista Colombiana de Entomología, 2010)
The Biological Control Laboratory of Corpoica developed two formulations based on a native isolate of the Phthorimea operculella granulovirus isolated from Tecia solanivora larvae, for the control of these moths in the field. These formulations include a UV protector from the group of optical brighteners. To determine the effect of the brightener, viral suspensions adjusted to five concentrations from 102 up to 106 CI/mL were prepared in brightener solutions at 0.1% and 0.5% and a bioassay was performed to determine the viral  LC50. Afterwards the two formulations, an emulsifiable concentrate and a dispersible granule, were applied on potato tubers that were exposed to ultraviolet radiation during two, four, six, eight, and 10 hours and a bioassay was performed to determine viral inactivation level by evaluating insect mortality. Higher viral activity was observed when brightener concentration was increased, obtaining a LC50 of 1.6 x 106 CI/mL for pure virus, 3.0 x 105 CI/ mL for the virus with the photoprotector at 0.1% and 3.0 x 104 CI/ mL for the virus with the photoprotector at 0.5%, results that allow us to suggest the optical brightener presents a synergistic effect with the virus. Both formulations efficiently protected the virus from the effect of UV radiation, obtaining corrected mortalities of 60% after 10 hours of exposure with the emulsifiable concentrate, 46.6% with the dispersible granule and 23.3% with the pure virus.